A razão de nomear : o papel da identidade étnica na denominação dos logradouros de Caxias do Sul - Silva, Manuela Damiani Poletti da (My University, 2014)
The question of identity plays a significant role in any study made about the social, cultural and political reality of Caxias do Sul. Among the many identities that have been affected by and involved in shaping such a reality, the ethnical identity is of utmost importance, for the city was formed by the coming together – and sometimes the confrontation – of two main ethnicities: the Portuguese-Brazilian and the Italian-Brazilian ones. This paper focuses on identity, in its continuous shaping and reshaping process, as well as on the role it plays in the naming of streets and in the changes of such names that have taken place throughout the years in the community. Through the use of a qualitative bibliographical research, the reasons why the people in charge of naming the streets in Caxias do Sul have chosen names of characters unknown to the local inhabitants are presented. Besides, it is possible to notice the way the identity of the local ethnical groups was created by analyzing the process of changes of names of streets and squares in the downtown area of Caxias do Sul, which comes to prove that the ethnical identity has had a relevant role in the naming of streets and in the changes in their names that have taken place throughout the history of Caxias do Sul.
A questão da identidade assume papel de destaque em qualquer estudo que se realize sobre a realidade social, cultural e política de Caxias do Sul. E, dentre as inúmeras identidades que se processaram e se processam na construção de tal realidade, a identidade étnica é crucial, uma vez que a cidade foi moldada a partir do encontro – e por vezes do confronto- de duas principais etnias: a luso-brasileira e a ítalo-brasileira. A presente dissertação tem por tema a identidade, em seu contínuo processo de construção e reconstrução, além do importante papel que a mesma exerce na denominação dos logradouros e na troca de seus nomes ocorrida no decurso do tempo na comunidade. Através de uma pesquisa bibliográfica de caráter qualitativo, apresentam-se os motivos que teriam conduzido os denominadores a atribuir aos logradouros de Caxias do Sul nomes de personagens desconhecidos, não identificáveis pelos habitantes do lugar. Além disso, pode-se verificar a maneira como foi gerida a identidade dos grupos étnicos locais no processo de trocas dos denominativos de ruas e praças do centro urbano de Caxias do Sul, o que demonstra que a identidade étnica teve papel de relevância na denominação e na(s) substituição(ções) que se processaram ao longo da história de Caxias do Sul.
Keywords: Toponímia; Caxias do Sul (RS); Nomes geográficos; Etnicismo; Identidade social